2020
DOI: 10.3354/meps13527
|View full text |Cite
|
Sign up to set email alerts
|

Beyond a single patch: local and regional processes explain diversity patterns in a seagrass epifaunal metacommunity

Abstract: Ecological communities are jointly structured by dispersal, density-independent responses to environmental conditions, and density-dependent biotic interactions. Metacommunity ecology provides a framework for understanding how these processes combine to determine community seagrass meadows along the British Columbia coast. We tested the hypothesis that eelgrass Zostera marina L. epifaunal invertebrate assemblages are influenced by local environmental conditions but that high dispersal rates at larger spatial s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 83 publications
(57 reference statements)
1
12
0
Order By: Relevance
“…In the absence of direct estimates of connectivity that can include oceanographic currents, these studies have inferred dispersal limitation from comparisons of community composition over Euclidean distances. Stark et al (2020) found low turnover in community composition over 1,000 km of coastline which suggests that dispersal is not limiting the presence of species in seagrass meadows in this region and that most meadows are likely connected by dispersal at least often enough to rescue populations from stochastic extinction. While our results show low probabilities for long distance connections, we found a large number of possible short-distance connections and few completely isolated meadows.…”
Section: Seagrass Metacommunity Dynamicsmentioning
confidence: 84%
See 4 more Smart Citations
“…In the absence of direct estimates of connectivity that can include oceanographic currents, these studies have inferred dispersal limitation from comparisons of community composition over Euclidean distances. Stark et al (2020) found low turnover in community composition over 1,000 km of coastline which suggests that dispersal is not limiting the presence of species in seagrass meadows in this region and that most meadows are likely connected by dispersal at least often enough to rescue populations from stochastic extinction. While our results show low probabilities for long distance connections, we found a large number of possible short-distance connections and few completely isolated meadows.…”
Section: Seagrass Metacommunity Dynamicsmentioning
confidence: 84%
“…While our results show low probabilities for long distance connections, we found a large number of possible short-distance connections and few completely isolated meadows. Therefore, much of the Salish Sea could be connected through multi-generational steppingstone dispersal to connect distant meadows, which could explain the community composition patterns found in Stark et al (2020). Additionally, Stark et al (2020) found that the subset of taxa present in all sampled meadows represented multiple dispersal strategies, and no one strategy dominated cosmopolitan taxa.…”
Section: Seagrass Metacommunity Dynamicsmentioning
confidence: 97%
See 3 more Smart Citations